分布型水文モデルによるレナ川流域の長期流出解析 - 八田, 茂実; 早川, 博; 朴, 昊澤; 山崎, 剛; 山本, 一清; 太田, 岳史 (JOURNAL OF JAPAN SOCIETY OF HYDROLOGY AND WATER RESOURCES, 2009)
本研究ではレナ川流域を対象に長期間の日単位河川流量を推定できる水文モデルの構築を目的とした． 本研究で構築した水文モデルは，植生・積雪・土壌の熱・水交換を考慮できる陸面モデルと，河道網上の洪水追跡による流出モデルから構成され，陸面モデルで計算された土壌からの流出水が流出モデルの入力値となる．対象流域では，遅い流出成分と冬季間の河川氷が流出に大きな影響を与えている．このため，流出モデルでは，1）陸面モデルで計算された流出水の30 ％を遅い流出成分として，貯留関数を介して流出モデルの入力として与えること，2）河川氷厚を同時に計算し，結氷していない部分を流下させることによってその影響を考慮した． 本研究で構築した水文モデルを1987年から2003年までの期間に適用した結果，全期間に渡ってハイドログラフをほぼ再現できることを確認した．この結果は，本研究で構築した水文モデルが北方圏の河川における水循環のシミュレーションに有用なものであることを示している． The objective of this study is to develop a hydrological model that can estimate daily discharge over a long period of the Lena River basin. The hydrological model developed by this study is composed of a land surface model that can take the heat/water exchange of the vegetation, snow and soil into consideration and an runoff model based on the flood routing in the river channel network, with the outflow water from the soil calculated by the land surface model to be the input value to the runoff model. In the Lena River basin, the slow components of stream flow and the river ice during winter season have large effects to the hydrograph. Taking their effects into consideration, the following 2 processes were added to the runoff model; 1) 30 % of the outflow from the soil calculated by the land surface model regarded as the slow outflow component was given as the input to the outflow model through the storage function model and 2) The river ice thickness was calculated, letting the unfrozen portion flow down. The stream discharge was calculated for the period from 1987 to 2003 using the above hydrological model, and as a result, it was possible to exactly reproduce the actual measured hydrograph throughout the entire period. The results show that the hydrological model developed in this study is effective for simulation of the water cycle in the Northern Regions. journal article